THE ROLE OF RENOVATION IN IMPROVING THE QUALITY OF THE HOUSING FUND - Tаlipova Nargiza Zukhritdinovna; Uzakova Umida Ruzievna; Samiev Shokhrukh Fahriddin ugli (Galaxy International Interdisciplinary Research Journal, 2022)
The article deals with the issues of improving the consumer and economic characteristics of a dwelling during renovation. Information is given on the renovation of the housing stock, which plays a major role in improving the quality of housing and meeting the needs of the population in housing. An analysis of the methods of renovation of the housing stock was made